Low-Magnitude High-Frequency Vibration Accelerated the Foot Wound Healing of n5-streptozotocin-induced Diabetic Rats by Enhancing Glucose Transporter 4 and Blood Microcirculation - Yu, Caroline Oi-Ling (Sci Rep, 2017)
Delayed wound healing is a Type 2 diabetes mellitus (DM) complication caused by hyperglycemia, systemic inflammation, and decreased blood microcirculation. Skeletal muscles are also affected by hyperglycemia, resulting in reduced blood flow and glucose uptake. Low Magnitude High Frequency Vibration (LMHFV) has been proven to be beneficial to muscle contractility and blood microcirculation. We hypothesized that LMHFV could accelerate the wound healing of n5-streptozotocin (n5-STZ)-induced DM rats by enhancing muscle activity and blood microcirculation. This study investigated the effects of LMHFV in an open foot wound created on the footpad of n5-STZ-induced DM rats (DM_V), compared with no-treatment DM (DM), non-DM vibration (Ctrl_V) and non-DM control rats (Ctrl) on Days 1, 4, 8 and 13. Results showed that the foot wounds of DM_V and Ctrl_V rats were significantly reduced in size compared to DM and Ctrl rats, respectively, at Day 13. The blood glucose level of DM_V rats was significantly reduced, while the glucose transporter 4 (GLUT4) expression and blood microcirculation of DM_V rats were significantly enhanced in comparison to those of DM rats. In conclusion, LMHFV can accelerate the foot wound healing process of n5-STZ rats.